Pro-oxidant/antioxidant balance controls pancreatic β-cell differentiation through the ERK1/2 pathway - Hoarau, E (Cell Death Dis, 2014)
During embryogenesis, the intrauterine milieu affects cell proliferation, differentiation, and function by modifying gene expression in susceptible cells, such as the pancreatic β-cells. In this limited energy environment, mitochondrial dysfunction can lead to overproduction of reactive oxygen species (ROS) and to a decline in β-cell function. In opposition to this toxicity, ROS are also required for insulin secretion. Here we investigated the role of ROS in β-cell development. Surprisingly, decreasing ROS production in vivo reduced β-cell differentiation. Moreover, in cultures of pancreatic explants, progenitors were highly sensitive to ROS stimulation and responded by generating β-cells. ROS enhanced β-cell differentiation through modulation of ERK1/2 signaling. Gene transfer and pharmacological manipulations, which diminish cellular ROS levels, also interfered with normal β-cell differentiation. This study highlights the role of the redox balance on β-cell development and provides information that will be useful for improving β-cell production from embryonic stem cells, a step in cell therapy for diabetes.